2016
DOI: 10.3109/15563650.2016.1172082
|View full text |Cite
|
Sign up to set email alerts
|

Deaths by poisoning in Norway 2003–2012

Abstract: Poisonings remain a significant cause of mortality by injury in Norway. Emphasis should be placed on following the trends closely, especially regarding methadone deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…We found that the largest decreases in poisoning mortality in China occurred in unintentional poisoning and suicide by pesticide. The 2016 crude poisoning mortality in China (7.4 per 100 000 people in males and 4.3 in females) is lower than previous reports for northern European countries (ranging from 7.9 to 22.4 per 100 000 people) 6 , 8 and the USA (16.2 in per 100 000 people). 2 Variations across countries may reflect cultural differences, including societal reactions to suicide and suicide risk, management of lethal and poisonous substances, living and work environments and the reporting quality of poisoning mortality data (such as under-reporting due to the stigma attached to suicide).…”
Section: Discussioncontrasting
confidence: 55%
“…We found that the largest decreases in poisoning mortality in China occurred in unintentional poisoning and suicide by pesticide. The 2016 crude poisoning mortality in China (7.4 per 100 000 people in males and 4.3 in females) is lower than previous reports for northern European countries (ranging from 7.9 to 22.4 per 100 000 people) 6 , 8 and the USA (16.2 in per 100 000 people). 2 Variations across countries may reflect cultural differences, including societal reactions to suicide and suicide risk, management of lethal and poisonous substances, living and work environments and the reporting quality of poisoning mortality data (such as under-reporting due to the stigma attached to suicide).…”
Section: Discussioncontrasting
confidence: 55%